The Frequency of Persisters in Escherichia coli Reflects the Kinetics of Awakening from Dormancy - Jõers, Arvi (American Society for Microbiology (ASM), 2010)
A genetically homogenous bacterial population may contain physiologically distinct subpopulations. In one such case, a minor part of an otherwise antibiotic-sensitive bacterial population maintains a nondividing state even in a growth-supporting environment and is therefore not killed by bactericidal antibiotics. This phenomenon, called persistence, can lead to failure of antibiotic treatment. We followed the development of sensitivity to killing by ampicillin and norfloxacin when Escherichia coli cells were transferred from a stationary-phase culture into fresh growth medium. In parallel, we monitored growth resumption by individual bacteria. We found that bacteria in a population resumed growth and became sensitive to antibiotics at different times after transfer to fresh medium. Moreover, both growing and dormant bacteria coexisted in the same culture for many hours. The kinetics of awakening was strongly influenced by growth conditions: inocula taken from the same stationary-phase culture led to very different persister frequencies when they were transferred into different fresh media. Bactericidal antibiotics kill cells that have woken up, but the later-awakening subpopulation is tolerant to them and can be identified as persisters when the antibiotic is removed. Our observations demonstrate that persister count is a dynamic measure and that the persister frequency of a particular culture is not a fixed value.